2022
DOI: 10.1161/svin.121.000331
|View full text |Cite|
|
Sign up to set email alerts
|

Current State of Stroke Care in Vietnam

Abstract: Stroke is the leading cause of death and disability in Vietnam. This review aims to assess the current status of the stroke care system and quality criteria in the acute phase at stroke hospitals. In 2016, the Ministry of Health in Vietnam issued Circular 47, a mandate to build stroke units in Vietnam. The ANGELS program, which is supporting the World Stroke Organization to gain its goals, was implemented in 18 stroke‐ready hospitals in Vietnam to help address quality of stroke patient care in 2017. From the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
1
11
0
3
Order By: Relevance
“…Although half of the neurointerventionalists in the survey were from middle-income countries, there were no participants from low-income countries. This may reflect both the lack of endovascular resources in these countries 44,45 and a sampling bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although half of the neurointerventionalists in the survey were from middle-income countries, there were no participants from low-income countries. This may reflect both the lack of endovascular resources in these countries 44,45 and a sampling bias.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while this survey captured many responses from across the globe, clinicians from Africa, South America, Central America, and Oceania were underrepresented. Given that these regions are home to many low-income and middle-income nations where advanced imaging may present an increased burden [ 35 ] due to its high cost, the perceptions of these clinicians can inform the divergent preferences between non-interventionists and interventionists in the acute management of patients with large vessel occlusion stroke presenting in the extended time window. Third, there was no external validation.…”
Section: Discussionmentioning
confidence: 99%
“…RESILIENT showed that good outcomes with EVT could be achieved in the public health system of Brazil, serving as a model for other low- or middle-income countries. 28 29…”
Section: History Of Trialsmentioning
confidence: 99%